Comparative International Communication Projects: Overcoming the Challenges - Esser, Frank (Brazilian journalism research, 2007)
Over the last 10-20 years, comparative research in the feld of communication has almost become fashionable. Many factors are responsible for this, for example: an increased awareness of globalisation as a communication-driven process; an awareness of increased transnational conglomerization of media organizations; and the increasing use of the Internet which facilitates easier access to information around the world. But the big question is how to organize collaborative international communication research efectively? Which models of cooperation are available to us, and what are their advantages and disadvantages? In this article, I analyze fve ways of doing collaborative researches and their respective challenges.